Trade and trade barriers in vaccines and inputs to vaccine production in the Asia-Pacific region - Pralok Gupta; Ayona Bhattacharjee (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2022)
The COVID-19 pandemic re-emphasized the role of vaccines in prevention and control of outbreaks and infectious diseases, but not all countries are able to produce them. Limited domestic capacities combined with other bottlenecks have often resulted in vaccine stockouts in many countries. In this context, international trade could be instrumental in overcoming challenges pertaining to vaccine availability. This study is an analysis of trade and trade barriers related to vaccines and vaccine inputs in the AsiaPacific region, the second largest regional trader of vaccine inputs. Using trade-related data of the Asia-Pacific region, we find that while there was high dependence of this region on vaccine imports from the rest of the world, there was significant intraregional trade in vaccine inputs during the last two decades. Analysis of tariff data shows that vaccines remained duty free or at low tariffs in many countries within this region while several non-tariff measures from the pre-COVID-19 period still continued. This study includes results from a primary survey of stakeholders concerned with vaccine production and trade in India. Being a significant player for vaccines in the Asia-Pacific region, experiences from India can provide substantial insights and takeaways for other trading nations. The interview results highlighted that tariffs were not particularly important for COVID-19 vaccines, but Non-Tariff Measures (NTMs) played a crucial role in vaccine trade. Our findings imply the need for diversification of import sources of vaccines and vaccine inputs; lowering of tariffs; reduction in export restrictions; promoting regulatory coherence to enhance intraregional trade of vaccines within the region; emphasizing the development of transportation and storage capabilities in poor countries in addition to ensuring the supply of vaccines through trade and the use of trade agreements to ease trade restrictions.
Keywords: F13; F14; 330; COVID-19; vaccines; vaccine inputs; trade barriers; non-tariff measures; Asia-Pacific